Rare Earth Elements Uptake by Synthetic Polymeric and Cellulose-Based Materials: A Review - Sanchez-Poblete, J; Salfate-Calderon, G (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Contemporary industrial processes and the application of new technologies have increased the demand for rare earth elements (REEs). REEs are critical components for many applications related to semiconductors, luminescent molecules, catalysts, batteries, and so forth. REEs refer to a group of 17 elements that have similar chemical properties. REE mining has increased considerably in the last decade and is starting an REE supply crisis. Recently, the viability of secondary REE sources, such as mining wastewaters and acid mine drainage (AMD), has been considered. A strategy to recover REEs from secondary water-related sources is through the usage of adsorbents and ion exchange materials in preconcentration steps due to their presence in low concentrations. In the search for more sustainable processes, the evaluation of synthetic polymers and natural source materials, such as cellulose-based materials, for REE capture from secondary sources should be considered. In this review, the chemistry, sources, extraction, uses, and environmental impact of REEs are briefly described to finally focus on the study of different adsorption/ion exchange materials and their performance in capturing REEs from water sources, moving from commercially available ion exchange resins to cellulose-based materials. © 2022 by the authors.